Research on Current Solid Mass Energy Storage (SGES) - Su Yichen (E3S Web of Conferences)
With the increasing environmental challenge posed by fossil fuel combustion, there has been a significant effort to develop alternative energy sources. In addition, hydropower, once considered as a perfect solution, has recently faced the criticism of deteriorating downstream aquatic habitat. As a result, energy sources that are susceptible to the environment, such as wind or solar, have become some of the few available options. This is accompanied by a raised demand on reliable and efficient energy storage technology. This paper examines solid mass energy storage (SGES), a newly developed energy storage technology by converting excess electricity into gravitational potential energy. The paper also lists out some of its most popular variation and relevant quantitative analysis. With a simple and straightforward mechanism, SGES has the potential to be furtherly improved and popularized for a wider range of application. However, as a newly developed concept, there are very few applicated cases of SGES. This causes a shortage in operational data and analysis on aspects such as facility lifespan, giving out a future research direction in this field.